Pendekatan dalam Integrasi Kurikulum Pondok Pesantren dan Madrasah: Studi di Pondok Pesantren Al-Hikmah Bandar Lampung - Azmi, Muhamad; Muhammad Akmansyah; Amiruddin Amiruddin (Sekolah Tinggi Ilmu Tarbiyah Bustanul `'Ulum Lampung Tengah, 2023)
Curriculum integration in islamic education refers to involves integrating the concepts and content of religius learning and general learning. This study outlines the integration of salaf Islamic boarding school education with the madrasah curriculum at Pondok Pesantren Al-Hikmah Bandar Lampung. This type of research is a type of qualitative research and data collection technique used snowball sampling for interviews, accompanied by observation and documentation. The data were analyzed using integrative and interactive techniques. This study found that the Islamic integrated curriculum in Pondok Pesantren Al-Hikmah Bandar Lampung was applied by combining the national curriculum with salaf islamic boarding school (pesantren salaf) education. The integration of madrasa and salaf Islamic boarding school curriculum is to open ourselves to the progress of the times where students are equipped with religious knowledge and general science. Implementation of curriculum integration with a social-religious approach by inserting religious moderation values in learning.